FAIRY TALES SEBAGAI MEKANISME BUDAYA UNTUK MENANAMKAN DAN MEMBENTUK PERAN GENDER YANG SALAH PADA ANAK - Fadlia, Faradilla Fadlia (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
This paper try to describe how the fairy tales story attempt to established value and constructed gender role. This research also seeks to see what is the message and value that conveyed and built when the reader or audience are watching the Fairy Tales. The hypothesis of this research that Fairy tales becomes a cultural mechanism for preserving gender role in children. This paper used the concepts of difference, hierarchy, privileges that established inequality and structure and agent theory. Furthermore he methodology that will be used in this research is a literature review